Treatment of small vestibular schwannomas using microscopic with endoscopic surgery: a single-center retrospective analysis - Peng Zhou; Jiandong Zhu; Liang Sun; Jinxin Lu; Chengyuan Ji; Zhengquan Yu; Jiang Wu; Jiyuan Bu (BMC Surgery)
Abstract Objective The aim of this study was to retrospectively analyze the clinical data of 24 patients with small vestibular schwannomas, explore the surgical outcomes, and summarize the surgical experience. Methods Patients with small vestibular schwannomas who underwent surgery between January 2019 and December 2022 at the Department of Neurosurgery of the First Affiliated Hospital of Soochow University were included. Clinical data from all patients were collected and analyzed. Results Total tumor resection was achieved in all patients. Microscopic surgery alone was sufficient for complete resection in 7 patients, while the remaining 17 patients required combined microscopic and endoscopic approaches for complete removal. At the final follow-up, 16 patients maintained preoperative facial nerve function, 6 patients experienced improvement, while 2 patients experienced deterioration. And there were 13 patients maintained preoperative hearing function, 9 patients experienced improvement, while 2 patients experienced deterioration. Compared with microscopic resection alone, there was no significant difference in the Facial nerve function and Hearing function of patients underwent microscopic and endoscopic resection. During the follow-up period, all patients showed favorable prognosis without disease progression. Conclusions Compared with microscopic surgery, the microscopic with endoscopic surgery for small vestibular schwannomas lead to the better results in the degree of tumor resection, with no difference in functional protection.